EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI JAGUNG MANIS (STUDI KASUS DI KELURAHAN KESIMAN KECAMATAN DENPASAR TIMUR) - Seru, Gaudensia; Kardi, Cening; Yudiarini, Nyoman (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2017)
The purpose of this research is to know: (1) Effect of Seed Production Factor, urea fertilizer, ponska fertilizer, manure and labor in Kesiman Village, and (2) Efficient Use of Seed Production Factor, urea fertilizer, ponska fertilizer, manure, farm work at Kelurahan Kesiman Denpasar Timur. The research was conducted by survey / interview, in Kelurahan Kesiman, This location was chosen purposively (purponsive), whereas while the determination of respondents selected simple random sampling (Simple Random Sampling). The production function performed in this research is the "Cobb Douglas" Production Function. Meanwhile, to know the efficiency of the use of production factors is done with the production value and production price used. Based on the result of the research, it can be concluded that the influence of input to production in farming shows that input of seed, urea fertilizer, manure, have a very significant effect on corn production, while the input of ponska fertilizer and labor is not significant. While efficiency of input input of seed, urea fertilizer, manure each value greater 1 (one) or not yet reached the efficiency of price.